ROLE OF SELENIUM SUPPLEMENTATION ON ANTIOXIDANT CHANGES IN WISTAR ALBINO RATS AFTER CHRONIC RESTRAINT STRESS - S, QAIRUNNISA; G, PURUSHOTHAMAN; P, MOHANAPRIYA; KUMBAKONAM NAGARAJAN, POORNIMA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Stress is a non-specific response of the body to any physical or physiological demand. Oxidative stress may occur due to imbalance between pro-oxidants and antioxidants. Restraint stress or immobilization has been used extensively as a stressor for the study of stress-related biological, biochemical, and physiological responses in animals. Nutritional treatment by exogenous supplementation of antioxidants like selenium reactivates which guard against the insult caused ROS during the repeated restraint stress. The objective of the study is to determine the role of selenium on antioxidant changes in Wistar albino rats after chronic restraint stress. Methods: Adult male Wistar albino rats weighing about 180–200 g were taken for the study and were divided into three groups – the control group (n=6) chronic restraint stress group (n=6) and chronic stress treated with selenium (n=6). Restraint stress was given in wire mesh restrainers for 30 days (6 h/day), and the blood from the jugular vein was collected for estimation of antioxidant status (Superoxide dismutase, Glutathione peroxidase, CAT, Vit C, and Vit E) in rats. Results: One-way analysis of variance statistical test was used to analyses the mean and SD among the groups. The rats pre-treated with selenium (p<0.001) showed a significant decrease in lipid peroxidation. In chronic restraint stress, albino rats administered with Selenium showed a significant increase (p<0.001) in enzymatic and non-enzymatic antioxidant activity when compared to controls. Conclusion: The effect of the Selenium acts as a antidote to counteract the effects of restraint stress and has significant therapeutic application in counter acting oxidative damage on Wistar albino rats.